2006
DOI: 10.1007/s00425-005-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

The diageotropica gene of tomato encodes a cyclophilin: a novel player in auxin signaling

Abstract: The single gene, auxin-resistant diageotropica (dgt) mutant of tomato displays a pleiotropic auxin-related phenotype that includes a slow gravitropic response, lack of lateral roots, reduced apical dominance, altered vascular development, and reduced fruit growth. Some auxin responses are unaltered in dgt plants, however, and the levels, metabolism, and transport of auxin appear normal, indicating that the Dgt gene encodes a component of a specific auxin signaling pathway. By combining map-based cloning with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 64 publications
2
91
0
14
Order By: Relevance
“…The unusual FK506-binding domain in TWD1 was instead found to participate in protein interaction with ABCB-type auxin transporters and is apparently involved in the functional regulation of these transporters [44] (see Section 4). TWD1 also possesses a tetratricopeptide repeat domain (common [131] Regulation and PM-to-ER trafficking of ABCB-type auxin transporters [8,9] Z. mais [133] Interaction with ABCB transporters on PM (via FKB-domain) [8,62], ABCC transporters on tonoplast (via TPR domain) [66], with HSP90 (TPR domain) [62,65] and calmodulin (calmodulin-binding domain) [66] Over-expression of TWD1 lacking its membrane anchor results in hypermorphic growth [64] FKBP72/PAS1 A. thaliana [69] Unclear (C-terminal membrane anchor), nuclear [68,134] Low, inhibited by FK506 and rapamycin [134] Up-regulated cell division, leaf fusions, short hypocotyls, sterile [69] O. sativa [131] Chaperon during translocation of NAC-like transcription factor (AtFAN) into nucleus [68] Z. mais [133] Regulation of very long fatty acid elongation [70] -DGT/CypA/ROC1/CYP1/CYP2/ P. patens [10] Nuclear and cytoplasmic [10,90], phloem sieve elements [79] Significant [77,78], inhibited by CsA [78] Regulates growth [90], gene expression [84,90,92], patterned cell division [88], phloem function [79], ROS balance in root apical meristem [87] A. [137] in many large immunophilins) that was shown to interact with vacuolar ABC transporters of the C subclass and HSP90 [65,66], as w...…”
Section: Plant Immunophilins Are Implicated In Regulation Of Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The unusual FK506-binding domain in TWD1 was instead found to participate in protein interaction with ABCB-type auxin transporters and is apparently involved in the functional regulation of these transporters [44] (see Section 4). TWD1 also possesses a tetratricopeptide repeat domain (common [131] Regulation and PM-to-ER trafficking of ABCB-type auxin transporters [8,9] Z. mais [133] Interaction with ABCB transporters on PM (via FKB-domain) [8,62], ABCC transporters on tonoplast (via TPR domain) [66], with HSP90 (TPR domain) [62,65] and calmodulin (calmodulin-binding domain) [66] Over-expression of TWD1 lacking its membrane anchor results in hypermorphic growth [64] FKBP72/PAS1 A. thaliana [69] Unclear (C-terminal membrane anchor), nuclear [68,134] Low, inhibited by FK506 and rapamycin [134] Up-regulated cell division, leaf fusions, short hypocotyls, sterile [69] O. sativa [131] Chaperon during translocation of NAC-like transcription factor (AtFAN) into nucleus [68] Z. mais [133] Regulation of very long fatty acid elongation [70] -DGT/CypA/ROC1/CYP1/CYP2/ P. patens [10] Nuclear and cytoplasmic [10,90], phloem sieve elements [79] Significant [77,78], inhibited by CsA [78] Regulates growth [90], gene expression [84,90,92], patterned cell division [88], phloem function [79], ROS balance in root apical meristem [87] A. [137] in many large immunophilins) that was shown to interact with vacuolar ABC transporters of the C subclass and HSP90 [65,66], as w...…”
Section: Plant Immunophilins Are Implicated In Regulation Of Developmentmentioning
confidence: 99%
“…For example, cyclosporine A was found to inhibit the PPIase activity of Arabidopsis chloroplasts stromal extracts [77], and Arabidopsis ROC1/CypA and tomato DIAGEOTROPICA (DGT/CypA) were sensitive to cyclosporine A in in vitro studies [78]. PPIase activity also seems conserved in plant cyclophilins, and strong activity has been experimentally demonstrated in all tested proteins, e.g., Interactions with DGT/CypA may be regulating PIN membrane exchanges and activity (left panel) [10,124].…”
Section: Plant Immunophilins Are Implicated In Regulation Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of plant CYP genes, mainly in Arabidopsis, have been functionally characterized, involved in a variety of physiological and developmental processes, including in flowering, phytohormone signalling, stress responses and immune responses [22][23][24][25][26][27] . Mutations in LRT2-like genes of the tomato DIAGEOTROPICA (DGT) and the moss Physcomitrella patens PpDGT genes also caused an auxin-resistant phenotype [28][29][30] , indicating that this class of highly conserved genes plays an important role in regulating auxin signalling in both lower and higher plants. However, how the cyclophilin-type PPIases function in auxin signalling remains unknown.…”
mentioning
confidence: 99%
“…25 Treatment of hypocotyl explants with CsA (10 µM) lead to formation of fewer number of roots which exhibited extension growth. Oh et al 26 reported a significant reduction in the number of roots in the presence of CsA in hypocotyl explants from tomato. Subjecting hypocotyl explants with a combination of CsA and IAA lead to formation of fewer number of root initials, reaffirming the involvement of NO in auxin action in the developmental process under investigation (AR).…”
Section: In Pharmacologicalmentioning
confidence: 99%